2013
DOI: 10.1371/journal.pone.0055354
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Enhanced Magnetic Resonance Imaging for Mapping of Whole Brain Activity Patterns Associated with the Intake of Snack Food in Ad Libitum Fed Rats

Abstract: Non-homeostatic hyperphagia, which is a major contributor to obesity-related hyperalimentation, is associated with the diet’s molecular composition influencing, for example, the energy content. Thus, specific food items such as snack food may induce food intake independent from the state of satiety. To elucidate mechanisms how snack food may induce non-homeostatic food intake, it was tested if manganese-enhanced magnetic resonance imaging (MEMRI) was suitable for mapping the whole brain activity related to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 50 publications
(63 reference statements)
1
41
0
1
Order By: Relevance
“…Although the feeding experiments were performed during the light cycle of the day, i.e., the resting phase of the rats (Hoch et al, 2013), considerable additional food intake was observed, which was dependent on the composition of the test food. A lack of side- or place-preference was observed when powdered STD was provided in both of the food dispensers resulting in a similar food and energy intake from both dispensers without significant difference ( p = 0.3311, Figures 3A,B; Tables 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the feeding experiments were performed during the light cycle of the day, i.e., the resting phase of the rats (Hoch et al, 2013), considerable additional food intake was observed, which was dependent on the composition of the test food. A lack of side- or place-preference was observed when powdered STD was provided in both of the food dispensers resulting in a similar food and energy intake from both dispensers without significant difference ( p = 0.3311, Figures 3A,B; Tables 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the REF diet was highly refined; that is, its ingredients had been broken down into simple components and reconstituted into compact pellets. There is evidence that the exact same nutrients dysregulate appetite and impair satiety mechanisms to promote obesity when ingested as refined flours instead of as whole foods [4,22,25,37]. It is likely that the aspects of the REF diet that are obesogenic and disrupt normal cognitive function will prove multifactorial in nature.…”
Section: Discussionmentioning
confidence: 99%
“…MEMRI combined with delivery of Mn 2+ with osmotic minipumps has been used recently for mapping brain activity in various behavioral tasks in rats (Eschenko et al 2010;Bangasser et al 2013;Hoch et al 2013). Here, we hypothesized that recruitment of neuronal circuits by voluntary alcohol drinking results in an alteration of functional activity that could be detected with MEMRI.…”
mentioning
confidence: 99%